Urban and Community Forestry in the Northeast - Kuser, John E.; Kuser, John E. (Springer Netherlands : Imprint: Springer, 2007)
Cover design by Susanne Van Duyne (Trade Design Group) Cover illustration depicts the USDA Plant Hardiness Zone.